2022
DOI: 10.1530/eje-22-0208
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the spectrum of steroidogenic enzyme inhibition between Osilodrostat and Metyrapone in ACTH-dependent Cushing syndrome patients

Abstract: Introduction: Osilodrostat is a new 11 ß-hydroxylase inhibitor with a mode of action analogue to Metyrapone. The objective of this study was to compare steroidogenic profiles in patients treated by either Osilodrostat or Metyrapone for ACTH-dependent Cushing’s Syndrome (CS). Methods: Patients followed in Cochin hospital Endocrinology department between March 2019 and December 2021 for an ACTH-dependent CS, controlled by either Osilodrostat or Metyrapone were included. A serum profile of 5 steroids (cortisol,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…This might be due to a stronger 17α‑hydroxylase (CYP17A1) and potentially cholesterol side chain cleavage enzyme and/or StaR protein inhibition, which has been proposed for osilodrostat ( 31 ) and verified in a recent publication. Bonnet-Serrano et al showed that in patients on osilodrostat but not on metyrapone, 21-hydroxylase and CYP17A1 activity were significantly decreased ( 32 ). In our small subgroup of patients on metyrapone, but not on osilodrostat medication, treatment also led to a significant elevation of classical androgens, in particular of A4, thus, confirming the in vitro and in vivo results.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to a stronger 17α‑hydroxylase (CYP17A1) and potentially cholesterol side chain cleavage enzyme and/or StaR protein inhibition, which has been proposed for osilodrostat ( 31 ) and verified in a recent publication. Bonnet-Serrano et al showed that in patients on osilodrostat but not on metyrapone, 21-hydroxylase and CYP17A1 activity were significantly decreased ( 32 ). In our small subgroup of patients on metyrapone, but not on osilodrostat medication, treatment also led to a significant elevation of classical androgens, in particular of A4, thus, confirming the in vitro and in vivo results.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenal androgens and mineralocorticoid precursor increase-related AEs are the main limitations of metyrapone use; however, they may occur in 42.3-58.4% of patients on osilodrostat, as previously mentioned [14,21]. Nevertheless, Bonnet-Serrano et al showed a smaller increase in 11-deoxycortisol and androgen concentrations in patients with osilodrostat compared with metyrapone therapy [36]. Additionally, mean levels of adrenal hormone precursors and androgens decreased during long-term osilodrostat treatment [23].…”
Section: Discussionmentioning
confidence: 93%
“…Isolated 11β-hydroxylase block leads to accumulation of precursors such as 11-deoxycortisol and androgens (androstenedione, testosterone and DHEA/DHEAS). Treatment by osilodrostat showed only mild androgen elevations when compared to metyrapone ( 12 ). In this patient DHEA, DHEAS decreased, while androstenedione and testosterone were slightly elevated during the osilodrostat treatment ( Table 2 ).…”
Section: Discussionmentioning
confidence: 94%
“…While osilodrostat was initially developed as an aldosterone synthase (CYP11B2) inhibitor, it was found to have strong 11β-hydroxylase (CYP11B1) inhibition and further clinical studies suggest that the drug also inhibits 17α-hydroxylase and 21-hydroxylase based on measured ratios of precursors/metabolites ( 12 ). Interestingly, when expressed alone, negligible inhibition of these enzymes occurred in vitro ( 13 ).…”
Section: Discussionmentioning
confidence: 99%